2020
DOI: 10.1021/acs.est.0c02922
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of HOCs via Precontaminated Microplastics by Earthworm Eisenia fetida in Soil

Abstract: Soil is a primary sink for plastics, but the influence of microplastics as carriers on terrestrial cycling of persistent contaminants is poorly understood as compared to aquatic systems. Studies to date have disregarded the potential fact that microplastics are generally contaminated before their entry into soil. In this study, earthworm Eisenia fetida was incubated for 28 d in a soil amended with five common types of microplastics precontaminated with polychlorinated biphenyls (PCBs) and polycyclic aromatic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Persistent organic pollutants (POPs) are a class of organic compounds that are resistant to environmental degradation and have detrimental effects on the environment and human health [ 166 ]. Given that POPs and M/NPs are all from the wastes of engineered products, they may coincidentally exist in some specific areas, such as farmland, fishpond, and raw sewage [ 167 ]. M/NPs may stably adsorb hydrophobic POPs such as polycyclic aromatic hydrocarbons (PAHs) [ 168 ], polychlorinated biphenyls (PCBs) [ 169 ] and dichlorodiphenyltrichloroethane (DDT) [ 170 ] on their surfaces to form surface coronas.…”
Section: Corona Formation On Micro/nanoplasticsmentioning
confidence: 99%
“…Persistent organic pollutants (POPs) are a class of organic compounds that are resistant to environmental degradation and have detrimental effects on the environment and human health [ 166 ]. Given that POPs and M/NPs are all from the wastes of engineered products, they may coincidentally exist in some specific areas, such as farmland, fishpond, and raw sewage [ 167 ]. M/NPs may stably adsorb hydrophobic POPs such as polycyclic aromatic hydrocarbons (PAHs) [ 168 ], polychlorinated biphenyls (PCBs) [ 169 ] and dichlorodiphenyltrichloroethane (DDT) [ 170 ] on their surfaces to form surface coronas.…”
Section: Corona Formation On Micro/nanoplasticsmentioning
confidence: 99%
“…In this context, some evidence has shown that micro(nano)plastics could increase the bioaccumulation of heavy metals Cu, Ni [ 52 ] and Cd [ 53 ], as well as HOCs dufulin [ 54 ], pyrene [ 55 ], PFOS and PFOA [ 56 ] in earthworms by enhancing their bioavailability. Conversely, other researchers suggested that microplastics, at amendment rates of ≥1% d.w., reduced the tissue concentrations of polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyl (PCB) in earthworms [ 34 ], and this could potentially be related to the fugacity gradient of chemicals between microplastics and soils [ 57 ]. In general, combined exposure can induce greater oxidative damage to earthworms compared with exposure to micro(nano)plastics or other pollutants alone, and, thus, negative effects on growth, behavior and the immune system of earthworms can be heightened [ 20 , 53 , 54 ].…”
Section: Analysis Of Hotspot Evolutionmentioning
confidence: 99%
“…Experiment Koelmans et al (2016) modelled the experiment published by Rochman et al (2013) with aqueous concentration set to zero and ingestion rate and concentrations in food set at the values reported in the study. This model framework has been developed, applied and validated (Table 6.5) in a series of studies (Koelmans et al 2013a(Koelmans et al , b, 2014(Koelmans et al , 2016Koelmans 2015;Rochman et al 2017;Wang et al 2019Wang et al , 2020a. A similar model has been applied by Bakir et al (2016) to assess the relative contribution of chemical uptake pathways for marine worms, fish and seabirds.…”
Section: Calculation Of the Contribution Of Plastic In The Laboratorymentioning
confidence: 99%